Biomarkers of exposure and effect in a lacertid lizard (Podarcis bocagei Seoane) exposed to chlorpyrifos - Amaral, Maria José (2019)
In Europe, reptiles have been recently included in environmental risk-assessment processes for registration of plant-protection products. However, data on toxicity effects of most compounds are lacking. Chlorpyrifos is the most commonly used organophosphorus insecticide worldwide. In the present study, the authors exposed a lacertid lizard, Podarcis bocagei, to sublethal concentrations of chlorpyrifos. Individuals were exposed through spiked food for a period of 20 d (low dose 0.12 mg/kg/d, high dose 1.57 mg/kg/d). After exposure, various biomarkers of exposure and effect were evaluated, including the activities of glutathione S-transferase and enzymes involved in the glutathione redox cycle, glutathione concentrations, activities of esterases, liver and testes histopathologies, as well as locomotory and predatory behavior. The results indicate that sublethal, subchronic exposure to chlorpyrifos can affect P. bocagei in a dose-dependent manner. Adverse effects occurred at both the subindividual and individual levels, including inhibition of carboxylesterases and cholinesterases (ChEs), liver histopathological changes, and altered predatory behaviors. Animals exposed to chlorpyrifos took more time to capture and subdue prey items. The results suggest a link between effects at subindividual levels of organization with those observed at the whole individual level after exposure to environmentally realistic dosages of chlorpyrifos.